COMMUNICATION FOR CONSUMERS PROTECTION IN PURCHASING GOODS AND SERVICES VIA ONLINE MEDIA - Thammanyutanun, Pavoranun; Lomchawakarn, Piyachat; Tokeaw, Wittayatorn; Sudhivoraseth, Jitraporn (Journal of Social Science and Cultural, 2024)
This research aims to study 1) The communication policy for consumer’s protection from purchasing goods and service through online platform 2) The communication problem for consumer’s protection from purchasing goods and service through online platform 3) The communication management from consumer’s protection from purchasing goods and service through online platform and 4) The proposal for communication development for consumer’s protection from purchasing goods and service through online platform. This study has been made by qualitative method through in-dept interview with the specified target group. The target group has filtered by selecting 33 persons from 5 group which directly related with consumer’s policy to the communication career which are 1) 9 people from the policy designing department 2) 9 people from consumer’s protection department 3) 5 people from consumer’s protection department in public company 4) 5 people from online entrepreneurs and 5) 5 people from online communication specialist academic. The research tools deployed in this study is the structural in-dept interview and data analytic. The study found that 1) The communication policy consisting of the proactive communication through all kinds of medias and people networking 2) The communication’s problem consisting of the lacking of exaggerated advertisement, complicated terms of law and less collaboration between the regulatory organizations 3) the communication management consisting of the participation on planning, partner networking collaboration and performance following up and evaluation by considering the complaint 4) the proposal for communication development consisting of regulatory organization should define all policy clearly. The seller should aware about consumer’s right, there should be more collaboration between consumer’s network and regulatory organization. The communication management should have a better planning and enhance it with the related organizations. The evaluation of communication’s result has to be made which including the development of the new model of the communication